TURKISH ALEVISM: RELIGIOUS IDENTIFICATION - D. V. Zhigulskaya (Vestnik MGIMO-Universiteta)
Alevis are forming a large religious community in Turkey. According to different estimations they compose 10 up to 20% of the country’s population. Their system of religious belief is called Alevism which is one of the heterodox Muslim sects. Formation of Alevism has completed in Anatolia in the XVI century. The philosophy, ritual and worship in Alevism extremely differ from those, which are attributed to dominant Islam of Turkey (Hanafi school of Sunni Islam).This article is dedicated to the question of religious identity of Alevism. Comparative method has been used in the article: it focuses on the problem of correlation between Alevism and Bektashism, which is considered to be another «popular Islam» of Anatolia;It should be mentioned that the terms of Alevism and Bektashism are often used as synonyms, which is incorrect. The question of possibility of ascribing Alevism to Shi’ism is also investigated in the article, as well as comparison of Alevism with Syrian Nusayri doctrine. It is well known that Nusayris of Syria are quite often called «Arab Alawites». This denomination causes misunderstanding between the wide range of readers. At the end of the article Alevism’s own place is finally being defined within the religious mosaic of Turkey.